Structural optimization of magnesium alloy vascular scaffolds for resistance to vascular plaque stress damage - Xin Shen; Jia She; Xianhua Chen; Chengzhi Duan; Senwei Wang; lei Shen; Fugui He (Materials & Design)
The majority of researchers primarily focused on the scaffold’s stress and strain in the design of biodegradable magnesium alloy scaffolds. However, in clinical applications, the flawed scaffold structure design will result in acute thrombosis and plaque rupture, which are factors that are often ignored in scaffold designs. In this research, we report on a new concept, taking vascular plaque stress damage as the design index of scaffold structure, and the finite element multi-objective neural network algorithm is responsible for the optimal design. Mg-xGd-5Y alloy with uniform degradation behavior is used as the basis of BMgS. Based on the observation of radial strength measurement, push measurement and collateral vessel passability measurement conditions verification, the optimized magnesium alloy scaffold was implanted into the coronary arteries of Bama minipigs. Quantitative optical coherence tomography (OCT) was used for observation at 1, 3, and 6 months of follow-up in vivo. Neither early restenosis nor thrombus were seen. The stress-induced damage of vascular plaque offers a novel methodology for the structural design of magnesium alloy scaffolds. Comprehensive validation of in vitro physical and in vivo biomechanical properties confirms the reliability of this approach, thereby advancing the development of biodegradable magnesium scaffolds.